Ankyrin-B reduction enhances Ca spark-mediated SR Ca release promoting cardiac myocyte arrhythmic activity - Camors, Emmanuel (2012)
Ankyrin-B (AnkB) loss-of-function may cause ventricular arrhythmias and sudden cardiac death in humans. Cardiac myocytes from AnkB heterozygous mice (AnkB(+/−)) show reduced expression and altered localization of Na/Ca exchanger (NCX) and Na/K-ATPase (NKA), key players in regulating [Na](i) and [Ca](i). Here we investigate how AnkB reduction affects cardiac [Na](i), [Ca](i) and SR Ca release. We found reduced NCX and NKA transport function but unaltered [Na](i) and diastolic [Ca](i) in myocytes from AnkB(+/−) vs. wild-type (WT) mice. Ca transients, SR Ca content and fractional SR Ca release were larger in AnkB(+/−) myocytes. The frequency of spontaneous, diastolic Ca sparks (CaSpF) was significantly higher in intact myocytes from AnkB(+/−) vs. WT myocytes (with and without isoproterenol), even when normalized for SR Ca load. However, total ryanodine receptor (RyR)-mediated SR Ca leak (tetracaine-sensitive) was not different between groups. Thus, in AnkB(+/−) mice SR Ca leak is biased towards more Ca sparks (vs. smaller release events), suggesting more coordinated openings of RyRs in a cluster. This is due to local cytosolic RyR regulation, rather than intrinsic RyR differences, since CaSpF was similar in saponin-permeabilized myocytes from WT and AnkB(+/−) mice. The more coordinated RyRs openings resulted in an increased propensity of pro-arrhythmic Ca waves in AnkB(+/−) myocytes. In conclusion, AnkB reduction alters cardiac Na and Ca transport and enhances the coupled RyR openings, resulting in more frequent Ca sparks and waves although the total SR Ca leak is unaffected. This could enhance the propensity for triggered arrhythmias in AnkB(+/−) mice.